SISTEM INFORMASI PENGARSIPAN PADA MTs NEGERI GEMBONG KAB. PATI BERBASIS MULTIUSER - ., Sunandar; ., Gesang Kristianto Nugroho (SPEED - Sentra Penelitian Engineering dan Edukasi, 2012)
Abstract : In an era of globalization growing technological developments, especially computer technology with centralized data archiving documents in the case.But not all schools have the facilities and infrastructure. As MTs are Gembong district. Starch, for this archive there are still using manual methods such as still using paper media as the main archive, which we often find difficult to find files because the data one by one so it takes a long time to find the record, and often the file is not found because the number of records that exist for many - years.From this research can facilitate archival system that runs there and minimize difficulties beam search, as the availability of Digital Archive Backup DataKeywords: Archives, Information Systems